A Political Theology of Glossolalia: Reconciling the Tongues of Babel, Jerusalem, and Corinth - Vondey, Wolfgang (Journal of pentecostal theology, 2024)
This article examines three biblical events with focus on the politics of language: the confusion of languages at Babel, the speaking in tongues at Pentecost, and the conflict of tongues and prophecies at Corinth. By identifying the ideology inherent in these passages and bringing them into conversation, the comparison aims at constructing a political theology of glossolalia that engages with the intersecting concerns of the sociopolitical and ideological identity of charismatic speech. The successive ideology found in the three events allows for the reading of the Babel narrative to inform the reading of Pentecost, and the two events together to inform the reading of Paul. The result highlights the importance of heteroglossia for resisting the reduction of inspired language to simply one tongue or many tongues and the suppression of any form of inspired speech to the quality of another.